Lead Electromigration In Flip Chip Packaging Under Hast Environment - Wong, Shaw Hwang (2004)
Failure under HAST condition will cause device malfunction. Lead migration can occur under HAST stress when two signals are biased. Lead migrates from solder bump to the adjacent copper trace in substrate causing electrical failure. The focus of this project is on the failure mechanism of the lead migration to understand how the lead migrates from bump.